1998
DOI: 10.1159/000053083
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone in the Treatment of Short Stature in Young Children with Intrauterine Growth Retardation

Abstract: Growth acceleration and bone maturation were studied in children with severe short stature and a history of intrauterine growth retardation (IUGR) to determine the effect of growth hormone (GH)-treatment. Patients were enrolled in an open randomized, multicenter trial and allocated to either the treated group (group 1, n = 38) or the control group (group 2, n = 31). Both groups were treated daily with 0.2 IU/kg/body weight during 3 years. The children in group 2 started the study with a 1-year observation peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…These data support Frost’s theory that muscle strength is a major determinant of bone metabolism [44]. In contrast, radial spongiosa and cortical bone densities do not correlate with muscular strength [39]. These data indicate that the main change in bone morphology during childhood is an increase in cortical thickness, throughout appositional growth, and the changes in bone geometry.…”
Section: Radial Bone Density Assessed By Peripheral Qctsupporting
confidence: 79%
See 3 more Smart Citations
“…These data support Frost’s theory that muscle strength is a major determinant of bone metabolism [44]. In contrast, radial spongiosa and cortical bone densities do not correlate with muscular strength [39]. These data indicate that the main change in bone morphology during childhood is an increase in cortical thickness, throughout appositional growth, and the changes in bone geometry.…”
Section: Radial Bone Density Assessed By Peripheral Qctsupporting
confidence: 79%
“…Augat et al [43]showed that the CSMI at the human radius correlated with fracture load at the femoral neck (r = 0.85). BSI increases with age and correlates with handgrip strength (measured by hand dynamometry), bone cross-sectional area and cortical area [39]. These data support Frost’s theory that muscle strength is a major determinant of bone metabolism [44].…”
Section: Radial Bone Density Assessed By Peripheral Qctmentioning
confidence: 56%
See 2 more Smart Citations
“…Altogether, the data suggest that preterm infants present a growth restraint pattern characterized by an extrauterine growth retardation that attenuates the catch-up growth and is responsible for the persistent short stature of these patients. Recombinant human GH (rhGH) therapy is a well-established treatment for SGA patients who fail to achieve spontaneous catch-up [12,13,14,15,16,17,18]. In SGA patients, GH treatment is able to increase IGF-I and IGFBP-3 concentrations [19].…”
Section: Introductionmentioning
confidence: 99%